Tempo poético e tempo prosaico: Uma oposição dialética da Estética de Hegel (Revista Eletrônica Estudos Hegelianos, 2017)
ABSTRACT: This article aims to show two opposite dimensions of time, present in Hegel’s Philosophy of Art, called respectively poetic time and prosaic time. This last is based on the Hegelian concept of “prose of the world” developed in his Aesthetics as a way of alienated production, work and life, while the first is based on the Hegelian concept of beauty as a way of overcoming that alienation. This paper also presents some theses of the German philosopher of the twentieth century Herbert Marcuse which can dialogue with the Hegelian theses. In order to facilitate the exposition of these theses, the article is divided into 3 parts, entitled: 1. Hegel’s thesis of the “prose the world” and the deduction of the concept of prosaic time; 2. Marcuse’s thesis about free time as sublation of the alienated work; 3. Hegel’s thesis of ideal beauty and the deduction of the concept of poetic time as sublation of the prosaic time. The final aim of this paper is to show the permanence of the prosaic time in our current historical reality and to discuss the possibility of the existence of a poetic time in our contemporaneity. This poetic time is conceived of as an alternative way of living freedom – not just as a free time and idleness, but as a creative time for cultural and artistic productions.